Position Statement on Atopic Dermatitis in Sub‐Saharan Africa: current status and roadmap. (12th November 2019) - Schmid‐Grendelmeier, P.; Takaoka, R.; Ahogo, K.C.; Belachew, W.A.; Brown, S.J.; Correia, J.C.; Correia, M.; Degboe, B.; Dorizy‐Vuong, V.; Faye, O.; Fuller, L.C.; Grando, K.; et al.
Abstract: Background: The first International Society of Atopic Dermatitis (ISAD) global meeting dedicated to atopic dermatitis (AD) in Sub‐Saharan Africa (SSA) was held in Geneva, Switzerland in April 2019. A total of 30 participants were present at the meeting, including those from 17 SSA countries, representatives of the World Health Organization (WHO), the International Foundation for Dermatology (IFD) (a committee of the International League of Dermatological Societies, ILDS www.ilds.org ), the Fondation pour la Dermatite Atopique, as well as specialists in telemedicine, artificial intelligence and therapeutic patient education (TPE). Results: AD is one of the most prevalent chronic inflammatory skin diseases in SSA. Besides neglected tropical diseases (NTDs) with a dermatological presentation, AD requires closer attention from the WHO and national Departments of Health. Conclusions: A roadmap has been defined with top priorities such as access to essential medicines and devices for AD care, in particular emollients, better education of primary healthcare workers for adequate triage (e.g. better educational materials for skin diseases in pigmented skin generally and AD in particular, especially targeted to Africa), involvement of traditional healers and to a certain extent also patient education, bearing in mind the barriers to effective healthcare faced in SSA countries such as travel distances to health facilities, limited resources and the lack of dermatological expertise. In addition, several initiatives concerning AD research in SSA were discussed and should be implemented in close collaboration with the WHO and assessed at follow‐up meetings, in particular, at the next ISAD meeting in Seoul, South Korea and African Society of Dermatology and Venereology (ASDV) meeting in Nairobi, Kenya, both in 2020.